Managing Systemic Banking Crises - Quintyn, Marc (International Monetary Fund, 2004)
Recent financial sector crises and their resolution have raised new issues and provided additional experiences to draw on in the future. Banking sector problems in Russia, Turkey, and a few Latin American countries occurred within the context of highly dollarized economies, high levels of sovereign debt, severely limited fiscal resources, or combinations thereof. These factors have challenged the effectiveness of many of the typical tools for bank resolution. This publication focuses on the issues raised in systemic crises, not on the resolution of individual bank problems. Based on the lessons learned during the Asian crisis, it updates the IMF's work on the general principles, strategies, and techniques for managing these crises